The first national report on the Bianchi technique for short bowel syndrome. : Two case reports. - Fein, Lucía; Sienra, Celina; Juambeltz , Carlos; Pereira-Nuñez Diego (Cirugía del Uruguay, 2025)
The Bianchi technique was effectively utilized to treat the first two documented cases of short bowel syndrome at the Pereira Rossell Hospital in Montevideo, Uruguay. Both cases involved type II short bowel syndrome (jejuno-colonic anastomosis), caused by a congenital factor (gastroschisis complicated with intestinal atresia) and were indicated by the persistent intestinal failure despite medical intervention. The outcomes were remarkably positive, resulting in the complete and permanent cessation of parenteral nutrition and substantial weight gain.